METODE MENGAJAR DALAM PENDIDIKAN ISLAM (Kajian Tafsir Tarbawi Surat An-Nahl: 125) - Syafrizal, Syafrizal; Charles, Charles; Juliwansyah, Juliwansyah; Rodi, Rodi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
Teachers use several strategies in achieving a learning goal. One of the teacher's steps to have this strategy is to master presentation techniques, or what is usually called the teaching method. Teaching methods are teaching methods that can be used to facilitate the transfer of knowledge to students, so that they are easily understood and understood. This paper aims to examine the existing teaching methods in Islamic Education. There are several teaching methods in Islamic education, including: the lecture method, the question and answer method, the demonstration and experiment method, the assignment method (recitation) and the group work method. Then according to Abdurahman An-Nahlawi, methods that can be applied in Islamic religious education include theQur'ani and Nabawi Hiwar (conversation) methods, the Qur'ani and Nabawi story methods, the Proverbs (parables) method, the Exemplary method, the Habituation method, the Ibrah and Mau'izzah methods, and the Targhib wa Tarhib method